Description of the mitochondrial genomes of Sichuan Tetrastes sewerzowi (Galliformes: Tetraonidae) and phylogenetic relationship - Xuequn Luo; Hang Zhou; Ao Li; Zhaoxia Huang; Wenping Zhang; Shizhang Du; Donglai Hua (Scientific Reports)
Abstract The Chinese Grouse (Tetrastes sewerzowi), a rare endemic bird in China, belongs to the Galliformes order and Tetraonidae family. Despite extensive research, subspecies classification remains inadequate, especially in Pingwu, Sichuan. This study sequenced the mitochondrial genome of T. sewerzowi in Wanglang Nature Reserve, Sichuan, analyzed its structural features, and reconstructed phylogenetic relationships within Tetraonidae. The results indicate that the high conservation in mitochondrial genome structure and sequence between the T. sewerzowi from Wanglang, Sichuan and Lianhuashan, Gansu indicates that they may belong to the same subspecies. Furthermore, we observed significant differences in the length of the mitochondrial control region between T. sewerzowi and Tetrastes bonasia. Based on the phylogenetic tree constructed using a comprehensive mitochondrial dataset, we propose the reclassification of the Hazel Grouse genus into two independent genera: Tetrastes and Bonasa. This study is the first to sequence the mitochondrial genome of T. sewerzowi from Sichuan and compare it with populations from Gansu, providing important insights into the distribution pattern of T. sewerzowi subspecies and facilitating the formulation of effective conservation strategies.